Swimming Learning Model in Developing Motor Skills of Children Aged 3-6 Years - Muhammad Ikhlasul Amal; Syahid Nuryasin; Ani Pristiawati (Journal of Physical and Outdoor Education, 2025)
This study aims to examine the effect of swimming learning models on the motordevelopment of children aged 3-6 years. Through the literature review method, this study analyzed various sources that discuss the effect of swimming learning on children's gross and fine motor skills. The results showed that implementing routine swimming interventions for six weeks was able to significantly improve gross and aquatic motor skills.This study also highlights the importance of effective learning models to improve children's learning processes and the role of parents and teachers in supporting motor development. Although a number of studies have shown positive aspects, more in-depth research is still needed regarding the long-term effects and transfer of swimming skills to everydaysituations. Methodological shortcomings and objective measurements are the mainobstacles in this study. Therefore, recommendations are directed at the development of more comprehensive methods and testing in a broader context.